THE FFECT OF IRRIGATION LEVELS ON SOME VEGETATIVE GROWTH PARAMETERS AND YIELD OF RICE UNDER DRY FARMING SYSTEM - & Salem, Hadi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field trial was carried out at the Rice Research Station in Mushkhab ( Najaf/ south of Iraq)State Broad for Agricultural Researches, during the Summer of 2013 in Clay Loam soil. The experiment was laid in split plot with two replications, to test the drought tolerance of different local and foreign varieties of rice .Rice varieties used were 6 varieties of aerobic rice from the International Rice Research Institute(IRRI) and local cultivars Anber33 and Jasmine. Two methods of irrigation ,flood irrigation, and 6 irrigation levels at "-10,-33,-50,-100 KPa" were used in this investigation .Studied parameters were: plant height ,spike length, flag leaf area, % of infertility , weight of 1000 grains and grain yield. Results indicated that varieties and irrigation treatments and their interaction had no significant differences on % of infertility and plant height .Varieties had significant effect on grain yield while irrigation treatment effected significantly on weight of 1000 grains. Interaction between varieties and irrigation had no significant effect on % of infertility , weight of 1000 grains and grain yield. Besides, irrigation treatments and varieties and their interaction had no significant effect on deltoid length.